PEMAHAMAN TEOLOGIS ORANG TUA KRISTEN TENTANG FORMASI IMAN ANAK DALAM KELUARGA DI GEREJA PROTESTAN MALUKU - Christina Metallica Samosir; Noh Ibrahim Boiliu; Meike Lely Lewankoru; Ribka Ribka; Eklin Amtor de Fretes (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
This study examines Christian parents’ perceptions of children’s faith formation within the family as an expression of Christian faith praxis in the context of the Protestant Church of Maluku. The study is grounded in the theological understanding that the family serves as a primary space for nurturing faith across generations within the life of the church. This research employs a qualitative approach using descriptive-analytical methods through interviews and document analysis involving church families. Data were analyzed thematically within the framework of practical theology and family theology. The findings indicate that parents perceive children’s faith formation as a spiritual responsibility closely related to life example, family worship practices, and the internalization of Christian values in daily life. However, contextual dynamics influence these practices, including social change, digital challenges, and limited theological understanding among families. This study contributes to the development of practical theology discourse, particularly in the areas of family theology and intergenerational faith formation within the context of local churches in Indonesia. Theologically, this study reaffirms the importance of the family as an essential space of faith praxis in sustaining church life and shaping the spirituality of younger generations.